2017
DOI: 10.17235/reed.2017.4237/2016
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic hematoma after ERCP: two new case reports

Abstract: ERCP is an endoscopic procedure with a complication risk ranging from 2.5 to 8%. The most frequent complications are pancreatitis, cholangitis, hemorrhage or perforation. Hepatic hematoma after ERCP is a potentially serious, rare complication. Not many cases are reported in the literature. We present here two new cases of hepatic hematoma following ERCP along with a review of the literature and possible therapeutic options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In these cases, most patients survived and only three patients deceased [6][7][8][9][10]. Although the mortality rate of complication could be low, it is still potentially lifethreatening.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, most patients survived and only three patients deceased [6][7][8][9][10]. Although the mortality rate of complication could be low, it is still potentially lifethreatening.…”
Section: Discussionmentioning
confidence: 99%
“…11 It is important to mention that early clinical presentation has been reported within the first 72 hours, and late after 7 days following ERCP; therefore, we conclude that it is not a complication following ERCP only of early presentation, and high clinical suspicion should be held in any patient regardless of the time of evolution. 12 Fernandez et al have reported a case of hepatic subcapsular hematoma as an incidental finding during laparoscopic cholecystectomy in a patient who had previously undergone ERCP for choledochal lithiasis, which shows that this pathology may be underdiagnosed. Abdominal computed tomography (CT) and magnetic resonance imaging (MRI) are useful; however, CT is the imaging method of choice, being able to characterize the lesion, define size, location and specific characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Second one, has greater logic due to the fact that so much pressure can be generated in the extraction, that the hepatic capsule and biliary complex when taken as a whole, can transmit the raw force of the operator. 4 Being a rare complication from the ERCP doesn't mean not to be energic treated or attended. Whatever the reason, the endoscopist should know, ERCP complications can be so complex to manage that even for a minimal procedure, and the patient can be admitted to intensive care.…”
Section: Discussionmentioning
confidence: 99%